2002
DOI: 10.1021/bi026540l
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Lipid-Binding Properties of Recombinant Human Surfactant Protein A Derived from One or Both Genes

Abstract: Surfactant protein A (SP-A) constitutes an important part of the innate immune defense in the lung. In humans there are two functional genes (SP-A1 and SP-A2). The functional importance of having two distinct chain types in human SP-A is undefined. Amino acid substitutions in the primary structure of the protein may have effects on structural stability or on activity. To address this issue, SP-A1, SP-A2, and coexpressed SP-A1/SP-A2 variants were in vitro expressed in insect cells, purified, and used for study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
141
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(156 citation statements)
references
References 60 publications
15
141
0
Order By: Relevance
“…Studies of host/guest triple helical peptides, where a single guest Gly-X-Y with substitutions in X and Y positions was studied while embedded in a collagen host peptide, showed that an Arg in the Y position associates with high stability of the host/guest peptide (9,61,73). Based on these studies, we have previously proposed (21,22) that Arg 85 (SP-A2) has a higher local microstability compared with Cys 85 (SP-A1). This may result in local "microunfolding" and exposure of SP-A1- specific epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of host/guest triple helical peptides, where a single guest Gly-X-Y with substitutions in X and Y positions was studied while embedded in a collagen host peptide, showed that an Arg in the Y position associates with high stability of the host/guest peptide (9,61,73). Based on these studies, we have previously proposed (21,22) that Arg 85 (SP-A2) has a higher local microstability compared with Cys 85 (SP-A1). This may result in local "microunfolding" and exposure of SP-A1- specific epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, qualitative and quantitative differences have been observed in vitro between the SP-A1 and SP-A2 genes (22,36,57,60,(77)(78)(79)(80)(81), pointing to the possibility that the overall functional activity of SP-A may depend on the relative SP-A1-to-SP-A2 levels rather than on the total SP-A content. To address this possibility, it .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations